Postnatal Germ Cell Development in the Cryptorchid Testis: The Key to Explain Why Early Surgery Decreases the Risk of Malignancy - Thorup, Jorgen; Clasen-Linde, Erik; Li, Ruili; Reinhardt, Susanne; Kvist, Kolja; Vikraman, Jaya; Southwell, Bridget R.; Hutson, John M.; Cortes, Dina (European Journal of Pediatric Surgery, 2018)
Purpose Cryptorchidism is a risk factor for testicular malignancy and surgical treatment lowers this risk. This study aimed to investigate the germ cell behavior in prepubertal cryptorchid testes using immunohistochemical markers for germ cell malignancy to understand how early orchiopexy may possibly prevent cancer developing.Materials and Methods Histology sections from 1,521 consecutive testicular biopsies from 1,134 boys aged 1 month to 16.5 years operated for cryptorchidism were incubated with antibodies including antiplacental-like alkaline phosphatase (PLAP), anti-Oct3/4, anti-C-kit, and anti-D2–40.Results Oct3/4 and D2–40-positive germ cells are found throughout the first 2 years of life, with declining frequency thereafter. After 2 years, they should have disappeared and may indicate neoplasia. PLAP-positive cells were seen in 57 to 82% and C-kit-positive cells in 5 to 21% of cryptorchid testes between 4 and 13 years. Not until puberty did PLAP and C-kit-positive undifferentiated spermatogonial stem cells vanish. Only 0.3% of the present material had obvious prepubertal intratubular germ cell neoplasia (ITGCN) and they all had syndromic cryptorchidism. An additional three boys (0.3%) older than 2 years had weak Oct3/4 expression in undescended testes, but all cases were D2–40 negative.Conclusion Prepubertal ITGCN was rare and mostly seen in syndromic cryptorchidism. In nonsyndromic cryptorchidism PLAP-positive undifferentiated spermatogonial stem cells persisted in a significant proportion of nontreated undescended testes and they will be especially sensitive to long-lasting abnormally high temperature that may be the single most important cause facilitating the accumulation of mutations during cell replication and the development of ITGCN to be prevented by orchiopexy.
Keywords: cryptorchidism; testicular cancer; intratubular germ cell neoplasia; immunohistochemistry; germ cells